Cervical trophoblasts for non-invasive single-cell genotyping and prenatal diagnosis. (January 2016) - Pfeifer, I.; Benachi, A.; Saker, A.; Bonnefont, J.P.; Mouawia, H.; Broncy, L.; Frydman, R.; Brival, M.L.; Lacour, B.; Dachez, R.; Paterlini-Bréchot, P.
Abstract: Objective: We aimed at developing a method to recover trophoblastic cells from the cervix through a completely non-invasive approach and obtaining a genetic proof of their fetal nature implying that they can be used for non-invasive prenatal diagnosis (NIPD). Methods: We studied obstetrical samples from 21 pregnant women between 8 and 12 weeks of gestation scheduled for chorionic villus sampling or undergoing elective termination of pregnancy. A cytobrush was used to extract cells from the external parts of the cervix and transferred to 10 ml of preservative solution. Cells were layered on filters with 8 microns pores using the ISET system (Isolation by SizE of Tumor/Trophoblastic cells) and stained. Putative fetal cells were collected by single cell laser-assisted microdissection and identified as fetal or maternal cells by Short Tandem Repeat genotyping. NIPD was blindly performed on 6 mothers at risk of having a fetus with Cystic Fibrosis or Spinal Muscular Atrophy. Results: Trophoblastic cells were recovered from all tested cervical samples with a frequency of 2–12 trophoblasts per 2 ml. NIPD was blindly obtained and verified in 6 mothers at risk of having a fetus with Cystic Fibrosis or Spinal Muscular Atrophy. Discussion: Although larger confirmation studies are required, this is the first report providing a solid proof of principle that trophoblasts can be consistently and safely recovered from cervical samples. Since they are a source of pure fetal DNA, i.e. fetal DNA not mixed with maternal DNA, they constitute an ideal target to develop NIPD of recessive diseases, which is a technical challenge for methods based on cell free DNA. Highlights: We provide methods for non-invasive prenatal diagnoses from cervical trophoblasts. We combined PAP-test sampling with ISET ® filtration and single-cell genotyping. Diagnoses of cystic fibrosis and spinal muscular atrophy were confirmed on 6 cases.